Analisis Pajak Penghasilan 21 di Indonesia: Teori, Implementasi dan Implikasinya - Nurul Jannah; Salsabila Putri; Yudi Paruhum (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Income Tax Article 21 (PPh Pasal 21) is a tax withheld on income received by resident individual taxpayers in connection with employment, services, or activities. PPh Pasal 21 plays a crucial role in Indonesia's taxation system as a pay-as-you-earn mechanism, ensuring stable and equitable state revenue. The subjects of PPh Pasal 21 include employees, pension recipients, former employees, members of the board of commissioners or supervisory board who are not permanent employees, and recipients of honoraria or other remuneration. The calculation of PPh Pasal 21 involves several components, including gross income, occupation costs, pension contributions, and Non-Taxable Income (PTKP). Effective implementation of PPh Pasal 21 requires a comprehensive understanding of relevant laws and regulations, as well as accuracy in calculation and reporting, to minimize compliance risks and tax disputes.